The Effects of Using a Guidance Activities Package Combining with Mindfulness Training to Develop Self-awareness of the High School Grade 9 Students at Maesaiprasitsart School in Chiangrai Province - Nantasit, Narenrid; Mekkhachorn, Nitipat; Na Ranong, Laddawan (Ratchaphruek Journal, 2021)
The purposes of this research were (1) to compare the levels of self-awareness of the students before and after using a guidance activities package combining with mindfulness training to develop self-awareness; and (2) to compare the level of self-awareness of the students who used the guidance activities package combining with mindfulness training to develop self-awareness with the level of self-awareness of the students who engaged in normal guidance activities. The research sample consisted of 40 Mathayom Suksa III students of Mae Sai Prasitsart School during the first semester of the 2019 academic year, obtained by cluster sampling with the use of classroom as the sampling unit. Then, the two classrooms were randomly assigned as the experimental and control groups, each of which containing 20 students. The employed research instruments comprised of a self-awareness assessment scale, a guidance activities package combining with mindfulness training to develop self-awareness, and a set of normal guidance activities. Statistics employed for data analysis were mean, standard deviation, and t-test. The research results showed that: (1) after the experiment, the post-experiment self-awareness level of the experimental group students was significantly increased over its pre-experiment counterpart level at the .01 level of statistical significance; and (2) after the experiment, the post-experiment self-awareness level of the experimental group students was significantly higher than the post-experiment counterpart level of the control group students at the .01 level of statistical significance.